Pengembangan Media Pembelajaran Interaktif berbasis Articulate Storyline 3 Pada Tema 8 Subtema Manusia dan Lingkungan - Safitri, Destriani; Suchyadi, Yudhie; Purnamasari, Ratih (UNIB Press, 2023)
This research is Research and Development (RnD), with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model which aims to develop and determine the feasibility of Interactive Learning Media using Articulate Storyline 3 on Theme 8 sub-theme humans and the environment. The feasibility of Interactive Learning Media is proven through the results of expert validation which is then tested in a limited trial and evaluation stage through the distribution of material questions and student response questionnaires. The validation test results from media experts, language experts and material experts stated that the product was in the